On the Dating of Theodor Studit “Delivered Sermons (Oglasitelnyje Pouchenija)” (Library of the Academy of Sciences of Lithuania F21-798) - Морозова, Н. (Kalbotyra, 1997)
In all Church Slavonic manuscript’s catalogs this codex unjustifiably is dated at 1476. The analysis of the historical and chronological data, presented in the copyist’s postscript, and paper’s watermark let conclude, that codex F21-798 was written about 1500.